Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1975
DOI: 10.1038/ki.1975.104
|View full text |Cite
|
Sign up to set email alerts
|

Permselectivity of the glomerular capillary wall: III. Restricted transport of polyanions

Abstract: The clearance of albumin relative to that of inulin is greatly exceeded by that of uncharged dextrans of the same effective molecular radius (approximately 36A), less than 0.01 vs. 0.20 in normal hydropenic rats. This marked difference in fractional clearances of albumin and neutral dextran suggests that some factor in addition to molecular size retards the transglomerular passage of albumin. Since albumin is a polyanion in physiological solution, we tested the effect of charge on macromolecular permeability b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
147
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(152 citation statements)
references
References 21 publications
5
147
0
Order By: Relevance
“…Since molecules with a molecular mass of 15-17 kDa are hindered only slightly in their passage across the capillary wall it follows that leptin with a molecular size of 16 kDa would be essentially freely filtered (Skorecki et al 1986). This conclusion must be tempered, however, by the fact that an acidic protein such as leptin bearing negative charges would be expected to show some restriction in its passage across the glomerular membrane (Chang et al 1975, Zhang et al 1994.…”
Section: Discussionmentioning
confidence: 99%
“…Since molecules with a molecular mass of 15-17 kDa are hindered only slightly in their passage across the capillary wall it follows that leptin with a molecular size of 16 kDa would be essentially freely filtered (Skorecki et al 1986). This conclusion must be tempered, however, by the fact that an acidic protein such as leptin bearing negative charges would be expected to show some restriction in its passage across the glomerular membrane (Chang et al 1975, Zhang et al 1994.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of charge selectivity emerged from a series of now classic studies examining the clearance of tracers differing in charge. [1][2][3] The permeability of anionic tracers was lower than their neutral counterparts, whereas that of cationic forms was enhanced. It was concluded that an intrinsic or "fixed" negative charge in the capillary wall poses an electrostatic barrier to anionic plasma proteins, such as albumin.…”
mentioning
confidence: 99%
“…Alterations in the size and charge-dependent selectivity of the glomerular basement membrane (GBM) have been described in models of proteinuria (1)(2)(3)(4). Heparan sulfate proteoglycans (HSPG) that comprise a protein core covalently linked to glycosaminoglycan side chains, such as heparan sulfate (HS), are one of the most important constituents of the GBM (5).…”
mentioning
confidence: 99%